2008
DOI: 10.1037/0012-1649.44.2.544
|View full text |Cite
|
Sign up to set email alerts
|

The development of automatic numerosity processing in preschoolers: Evidence for numerosity-perceptual interference.

Abstract: Three experiments examined developmental changes in the automatic processing of numerosity and perceptual information using a nonsymbolic numerical Stroop paradigm. In Experiments 1 and 2 (E1 and E2), 4-, 5-, and 6-year-olds had to compare the numerosities or the total filled areas of collections of dots (E1) or bars (E2) varying along both dimensions. Experiment 3 replicated E2's results in 3-, 4-, and 5-year-olds. Results demonstrated the existence of reciprocal influences between numerical and perceptual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
84
5
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 70 publications
(119 reference statements)
16
84
5
4
Order By: Relevance
“…A lot of possible powerful predictors besides the counting abilities were not taken into account in this research. Increasing evidence has been found for an important role of logic thinking abilities (e.g., Stock et al, 2007), numeracy (e.g., Desoete et al, 2004;Rousselle & Noël, 2008) and executive functions (e.g., Mazzocco & Kover, 2007;Van der Sluis, de Jong, & van der Leij, 2007) in the development of later arithmetic abilities. Fayol, Barrouillet and Marinthe (1998) found neuro-psychological tests to have good predictive value for performances on arithmetic tests in 5-to 6-year-old children.…”
Section: Discussionmentioning
confidence: 98%
“…A lot of possible powerful predictors besides the counting abilities were not taken into account in this research. Increasing evidence has been found for an important role of logic thinking abilities (e.g., Stock et al, 2007), numeracy (e.g., Desoete et al, 2004;Rousselle & Noël, 2008) and executive functions (e.g., Mazzocco & Kover, 2007;Van der Sluis, de Jong, & van der Leij, 2007) in the development of later arithmetic abilities. Fayol, Barrouillet and Marinthe (1998) found neuro-psychological tests to have good predictive value for performances on arithmetic tests in 5-to 6-year-old children.…”
Section: Discussionmentioning
confidence: 98%
“…Later on, the influence of parallel surface processing decreases (Rousselle & Noël, 2008) but even adults continue to be sensitive to perceptual dimensions in their numerical judgments (Gebuis & Reynvoet, 2012a, 2012bSzucs, Nobes, Devine, Gabriel, & Gebuis, 2013). Even if the majority of studies currently try to control the influence of perceptual variables when assessing non-symbolic magnitude processing Halberda, Mazzocco, & Feigenson, 2008;Mazzocco, Feigenson, & Halberda, 2011;Piazza et al, 2010;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004), the visual stimulus properties (e.g., surface, density) cannot be controlled for in each individual trial (Gebuis & Reynvoet, 2011, 2012a.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large number of studies have shown that numerical judgments are highly influenced by the visual perceptual properties of the stimulus (e.g. density, sum of perimeter, surface area, length, size…) in children and adults (Dormal & Pesenti, 2007;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Rousselle & Noël, 2008;Rousselle, Palmers, & Noël, 2004). Some studies even fail to find any evidence of a sensitivity to numerical differences when the perceptual variables, which naturally covary with numerosities, are strictly controlled for (Clearfield & Mix, 1999, 2001Feigenson, Carey, & Spelke, 2002;Mix, 2002;Rousselle et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Its existence has been shown consistently in number comparison or number discrimination tasks given to animals (e.g. Mechner, 1958;Platt & Johnson, 1971;Whalen, Gallistel, & Gelman, 1999;Gallistel & Gelman, 2000;Cantlon & Brannin, 2007), infants (Brannon, Abbot, & Lutz, 2004;Xu & Arriaga, 2007;Xu & Spelke, 2000), children (Rouselle & Noël, 2008;Sekuler & Mierkiewitz, 1977), and adults (for reviews see: Gallistel & Gelman, 2000;Feigenson, Dehaene, & Spelke, 2004;Dehaene, Molko, Cohen, & Wilson, 2004;Cantlon et al, 2008). The fact that the NDE is found across species and ages in number discrimination tasks suggests that we all share an evolutionary inherited, common representation of approximate numerical magnitudes.…”
mentioning
confidence: 93%